The Depiction of Nineteenth Century British Society in Literature Through Charles Dicken’s Our Mutual Friend - Oucheikh, Lydia; Soumani,Marwa; Bakhouche, Salah (University of Ammar Theledji -Laghouat, 2021)
Nineteenth century literature is highly concernedwith the daily life of the British society, specially the social novel. The problems of society are the major theme that is tackled by Victorian novelists. Charles Dickens‟ novel “Our Mutual Friend” portrays the conditions of the Victorian society and class division in that period. The present study is an attempt to describe the Victorian age and society and explore how the society was depicted in literature particularly the social novel. It also aims to show how “Our Mutual Friend” depicts the 19th century social issues. In order to achieve that the study relied on the thematic analysis of social issues in Dickens‟ novel “Our Mutual Friend”.Moreover, we used the critical concepts of Marxist LiteraryTheory to analyze the novel. The reason behind using this theory is that, itfocuses on social selections and also social conflict